2009
DOI: 10.1523/jneurosci.2955-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Coding of Visual Space during Motor Preparation: Approaching Objects Rapidly Modulate Corticospinal Excitability in Hand-Centered Coordinates

Abstract: Defensive behaviors, such as withdrawing your hand to avoid potentially harmful approaching objects, rely on rapid sensorimotor transformations between visual and motor coordinates. We examined the reference frame for coding visual information about objects approaching the hand during motor preparation. Subjects performed a simple visuomanual task while a task-irrelevant distractor ball rapidly approached a location either near to or far from their hand. After the distractor ball appearance, single pulses of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 60 publications
7
75
0
Order By: Relevance
“…In our study (Makin et al 2009), participants performed a simple button-press motor response with the right index Wnger, while a task-irrelevant three-dimensional ball suddenly fell just above the participants' responding hand. Using single-pulse transcranial magnetic stimulation (TMS) over the contralateral primary motor cortex, we found that the sudden appearance of this potentially threatening visual stimulus was associated with a reduction in corticospinal excitability at the very early and speciWc time window of 70-80 ms following its appearance (see Evarts 1974, for comparable response latencies in macaque M1 neurons, with respect to visual feedback for force application).…”
Section: Physiological Evidence For the Rapid Online Control Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study (Makin et al 2009), participants performed a simple button-press motor response with the right index Wnger, while a task-irrelevant three-dimensional ball suddenly fell just above the participants' responding hand. Using single-pulse transcranial magnetic stimulation (TMS) over the contralateral primary motor cortex, we found that the sudden appearance of this potentially threatening visual stimulus was associated with a reduction in corticospinal excitability at the very early and speciWc time window of 70-80 ms following its appearance (see Evarts 1974, for comparable response latencies in macaque M1 neurons, with respect to visual feedback for force application).…”
Section: Physiological Evidence For the Rapid Online Control Of Actionmentioning
confidence: 99%
“…When the target object was switched during movement execution, PMv pulses suppressed corticospinal excitability as early as 75 ms following the switch (which was time locked to the movement onset, right). a ModiWed from Makin et al (2009). b ModiWed from Buch et al (2010) body-part-centred representation is not restricted to visual space (e.g.…”
Section: Hand-centred Representations In Pmvmentioning
confidence: 99%
“…Previous studies investigated the representation of the peripersonal space by examining behavioral responses in patients with brain lesions (Farnè et al, 2000(Farnè et al, , 2005, probing reaction times during presentation of cross-modal stimuli near the body , and by registering changes in the excitability of the primary motor cortex to the presentation of objects near the hands (Makin et al, 2009). Here, we have taken a more direct approach and measured the BOLD-adaptation signatures of hand-centered encoding of space in the human brain.…”
Section: Discussionmentioning
confidence: 99%
“…lective processing of peri-hand visual stimuli (di Pellegrino et al, 1997;Farnè et al, 2000;Pavani and Castiello, 2004;Spence et al, 2004;Makin et al, 2009). An attentional account has been proposed as a possible interpretation for part of these behavioral findings (Spence et al, 2000Kennett et al, 2001), in line with the notion that peripersonal space and crossmodal spatial attention might share common mechanisms (Maravita et al, 2003;Driver and Noesselt, 2008).…”
Section: Dynamic Remapping Of the Hand-centered Representation Of Spacementioning
confidence: 99%
“…This suggests that in humans, as in primates, the selective perihand mechanism is used as an important interface for guiding hand actions toward objects within reaching distance (Brozzoli et al, 2011). Thus, the representation of the location of objects with respect to the hand could be used both to move the hand away from aversive objects (Makin et al, 2009) and to guide hand actions toward objects during reach-tograsp actions (Brozzoli et al, , 2010.…”
Section: A Spatial Representation For Hand-object Interactionsmentioning
confidence: 99%